Inspection Activities on Archaeological Sites in Milan. The Case of Imperial Mausoleum (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2015)
The project "Milano Archeologia" concerning the ancient remains of the city of Milan in Roman age was based on specific methods and tools, such as the collection of data through the previous archive research, and the feedback of information through inspections and then direct contact with monuments. A very interesting and significant case is the funerary complex area of “San Vittore al Corpo”, in which are also preserved the remains of an impressive Imperial Mausoleum. The curtain, that defines the space of the cemetery from the fourth Century AD, is kept in part below two modern buildings, while the remains of the Mausoleum are located below the present church of St. Victor. The analysis of the data collected allowed us to identify similarities and differences between the structures still visible, for example in the techniques adopted for the elevations or foundations, and it has provided the knowledge necessary to assume concrete solutions to protect and enhance this heritage.
Keywords: mausoleum; cemetery; archive; cultural heritage